IUU Fishing, Permasalahan Dan Upaya Pencegahannya Di Perairan Indonesia - Umi Raudah; Lili Pranola; Jayanti Wanda Anazatri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
IUU Fishing is a global issue in the world of fisheries, especially in Indonesian waters. The factors that cause IUU Fishing in Indonesian often occur are inseparable from the statement that Indonesian has potential and a strategic environtment in the global world, especially the condition of fisheries in other countries that have sea borders and fishery management systems in Indonesian. Factors causing IUU Fishing include the need for increased world fish demand, disparities in world fish prices, and overfishing. Losses experienced as a result of IUU Fishing in Indonesian can have social, economic, political and environmental impacts. In order to realize security in the marine and fisheries sector, orderly and uphold the law and human rights, it’s necessary to have efforts prevent and combat IUU Fishing, namely efforts to prevent, and take action.